Regulasi Penerapan Euthanasia di Indonesia dalam Perspektif Hak Asasi Manusia - Ayuning Tyas Azis Putri; Moh. Zeinudin (Jurnal Hukum dan Sosial Politik, 2024)
Humans must go through life events, including babies, children, teenagers, adults, the elderly and death. Death itself is a process that is greatly feared by humans. However, in the development of technology and science in the medical world, death does not come suddenly, death itself can occur with a plan, this action, namely killing in a predictable place and time, is called euthanasia, which is a killing process that is still controversial today. and has not been resolved properly by several parties. The aim of this research is: 1) To identify regulations for implementing euthanasia from a human rights perspective. 2). To identify the application of euthanasia in positive law in Indonesia. This research methodology uses normative juridical which includes primary, secondary and tertiary legal materials. The results of the research state that euthanasia regulations from a human rights perspective in Indonesian society believe that euthanasia is a practice that ignores a person's right to life and is not permitted, but the implementation of euthanasia already exists, which is called passive euthanasia, one of which is the act of doctors sending their patients home on the grounds that there is no treatment or desire. to recover still deserves to be punished if Indonesian law still prohibits euthanasia. However, this behavior does not violate the law, and often occurs in our society